Moderate to severe HIV-associated neurocognitive impairment: A randomized placebo-controlled trial of lithium. Issue 46 (November 2016) - Decloedt, Eric H.; Freeman, Carla; Howells, Fleur; Casson-Crook, Martine; Lesosky, Maia; Koutsilieri, Eleni; Lovestone, Simon; Maartens, Gary; Joska, John A.
Abstract : Supplemental Digital Content is available in the text Abstract: Background: HIV-associated neurocognitive disorder (HAND) remains highly prevalent despite effective anti-retroviral therapy (ART). A number of adjunctive pharmacotherapies for HAND have been studied with disappointing results, but preliminary data suggest that lithium may provide clinical benefit. In addition, the low cost of lithium would facilitate access in low- and middle-income countries which carry the greatest burden of HIV. Methods: Our objective was to evaluate the 24-week efficacy and safety of lithium in patients with moderate to severe HAND. Our primary efficacy endpoint was the change in Global Deficit Score (GDS) from baseline to 24 weeks, whereas our secondary endpoint was the change in proton magnetic resonance spectroscopy ( 1 H-MRS) brain metabolite concentrations. We conducted a 24-week randomized placebo-controlled trial of lithium as adjunctive pharmacotherapy. We enrolled participants with moderate to severe HAND, on ART for at least 6 months, with suppressed viral loads and attending public sector primary care clinics in Cape Town, South Africa. We randomized 66 participants to lithium (n = 32) or placebo (n = 34). Lithium or placebo was dosed 12-hourly and titrated to achieve the maintenance target plasma concentration of 0.6 to 1.0 mmol/L. Sham lithium concentrations were generated for participants receiving placebo. Results: Totally 61 participants completed the study (lithium arm = 30; placebo arm = 31). Participants at enrolment had a mean age of 40 years and a median CD4+ T-cell count of 500 cells/μL. The median change in GDS between baseline and week 24 for the lithium and placebo arms were –0.57 (95% confidence interval [CI] –0.77, –0.32) and –0.56 (–0.69, –0.34) respectively, with a mean difference of –0.054 (95% CI –0.26, 0.15); P  = 0.716. The improvement remained similar when analyzed according to age, severity of impairment, CD4+ count, time on ART, and ART regimen. Standard 1 H-MRS metabolite concentrations were similar between the treatment arms. The study drug was well tolerated in both study arms. Six serious adverse events occurred, but none were considered related to the study drug. Conclusion: Adjunctive lithium pharmacotherapy in patients on ART with HAND was well tolerated but had no additional benefit on neurocognitive impairment.